PENGOLAHAN PRODUK ABON IKAN LELE UNTUK PENINGKATAN PENDAPATAN MASYARAKAT DESA PENEN KECAMATAN SIBIRU-BIRU KABUBATEN DELI SERDANG SUMUT - Miranti Miranti; Mahyu Danil; Muhammad Nuh; Susan Novrini; Wan Bahroni Jiwar Barus; Apriawati Apriawati (Jurnal Pengabdian Mitra Masyarakat, 2022)
Abon catfish product is a very promising business to increase people's income in Penen Village, Kec. Sibiru-Blue North Sumatra. This shredded catfish business will help meet the high demand for fish in the market, creating opportunities for entrepreneurship in the fish farming sector. The stable catfish market has made catfish farming in demand. Catfish which is easy to develop is one of the supporting factors for the progress of catfish cultivation, and the level of catfish resistance to good weather changes supports the rapid development and convenience of farmers to make catfish farming the right choice for business. This community service aims to conduct a business feasibility study on the enlargement of catfish farms for the Penen Village community in terms of aspects related to the feasibility study. This feasibility study is expected to be able to find out the amount of investment funds needed, the existing market, and what obstacles may occur in the process of establishing this type of catfish processed business.